Creating Fake Identity and Pseudo Accounts on Social Media Among University Students in North Cyprus - Akdeniz, Ümit (Eastern Mediterranean University, 2018)
ABSTRACT: The study investigates the attitudes of international university students in Turkish Republic of North Cyprus through users’ creation fake identity on social media. This study aims to know if Facebook users check accounts if they are fake before they accept friend request, how Facebook users identify accounts as fake, if most Facebook active users create fake identity and create hyper real image of themselves. This study also seeks to know how users perceive other people who create fake identity on Facebook and if there is a statistical significant difference as to how male and female students perceive other people who create fake identity on Facebook. Through a survey conducted among seven hundred and sixty-seven international university students in Turkish Republic of North Cyprus; two hundred Eastern Mediterranean University students, one hundred and ninety-nine Near East University students, one hundred and ninety-two European University of Lefke and one hundred seventy-six Girne American University students enrolled in Fall 2017/2018 session. Results show that majority of the respondents agree to a very great extent that they check any account if its fake once they get a friend request. Results also show that respondents agree that they believe that an account is fake when it has exaggerated biography, profiles without photo, accounts with no mutual friends, mutual friends but any of mutual friends knows the person, accounts with few friends (i.e. 10-15 friends), empty timeline (No sharing) and extremely gorgeous human photo (beautiful/handsome). Results show that most respondents don’t create fake account and create hyper-real image of themselves. Results show that when respondents were asked how they perceive users who create fake identity, many respondents agree that they view people who create fake identity on Facebook as fraudsters, people who suffer from poverty of ideas, with low self esteem, inferiority complex, high level of insecurity, who wants to be acceptable by the society and attention seekers. Keywords: Social media, Facebook, Pseudo accounts, Hyper-real image, fake identity.

ÖZ: Bu çalışma, Kuzey Kıbrıs Türk Cumhuriyeti’nde yaşayan uluslararası üniversite öğrencilerinin, sosyal medyada sahte kimlik oluşumu üzerindeki tutumlarını incelemektedir. Araştırma sosyal medya kullanıcılarının arkadaşlık isteklerini kabul etmeden hesabın sahte olup olmadığına bakıp bakmadığını, sahte hesapları nasıl tespit ettiklerini, sahte hesabı nasıl tanımladıklarını ve çoğu kullanıcının sahte hesap açıp kendilerinin hiper-gerçek imajını yaratıp yaratmadıklarını inceliyor. Aynı zamanda kullanıcıların sahte hesabı olan insanları nasıl algıladığını ve bu algının erkek ve kadın öğrencilerde dikkate değer istatistiksel farklılıklar gösterip göstermediğini inceliyor. Araştırma için uygulanan ankete Kuzey Kıbrıs Türk Cumhuriyeti’nde, 2017/2018 Güz Dönemi için kayıtlı olan 767 uluslararası üniversite öğrencisi katılmıştır. Bu sayının 200’ü Doğu Akdeniz Üniversitesi’nde, 199’u Yakın Doğu Üniversitesi’nde, 192’si Lefke Avrupa Üniversitesi’nde ve 176’sı Girne Amerikan Üniversitesi’nde eğitim görmektedir. Sonuçlar katılımcıların çoğunun arkadaşlık isteği aldığında hesabın sahte olup olmadığına baktıklarını göstermektedir. Öğrencilerin çoğu, sahte olan hesaplarda abartılmış biyografiler içeren, fotoğrafsız hesaplar, ortak arkadaş olmayan veya ortak arkadaşların arasında kimsenin kişiyi tanımadığı, az arkadaşa sahip hesap (örneğin 10- 15 arkadaş), boş zaman tüneli olan (paylaşımı olmayan) ve son derece çekici insan fotoğrafı bulunan profiller olduğuna inanmaktadır. Sonuçlara göre katılımcıların çoğu sahte hesap açmıyor ve kendilerinin bir hiper-gerçek imajını yaratmıyorlar. Birçok katılımcıya göre Facebook’ta sahte kimliği olan insanlar sahtekar, kötü fikirleri olan, kendine saygısı az olan, aşağılık kompleksi olan , kendine güveni olmayan, toplum tarafından kabul edilmek istenen ve ilgi çekmeye çalışan insanlardır. Anahtar Kelimeler: Sosyal medya, Facebook, Sahte hesaplar, hiper-gerçek resim, sahte kimlik.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2018. Supervisor: Assist. Prof. Dr. Aysu Arsoy.
Keywords: Communication and Media Studies Department; Social Media - Students - Cyprus, North; Social media, Facebook, Pseudo accounts, Hyper-real image, fake identity